Lamin A mutation impairs interaction with nucleoporin NUP155 and disrupts nucleocytoplasmic transport in atrial fibrillation. Issue 3 (8th December 2018) - Han, Meng; Zhao, Miao; Cheng, Chen; Huang, Yuan; Han, Shengna; Li, Wenjuan; Tu, Xin; Luo, Xuan; Yu, Xiaoling; Liu, Yinan; Chen, Qiuyun; Ren, Xiang; et al.
Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia. Here, we show the identification and functional characterization of one AF‐associated mutation p.Arg399Cys in lamin A/C. Co‐immunoprecipitation and GST pull‐down assays demonstrate that lamin A/C interacts with NUP155, which is a nucleoporin and causes AF when mutated. Lamin A/C mutation p.Arg399Cys impairs the interaction between lamin A/C and NUP155, and increases extractability of NUP155 from the nuclear envelope (NE). Mutation p.Arg399Cys leads to aggregation of lamin A/C in the nucleus, although it does not impair the integrity of NE upon cellular stress. Mutation p.Arg399Cys inhibits the export of HSP70 mRNA and the nuclear import of HSP70 protein. Electrophysiological studies show that mutation p.Arg399Cys decreases the peak cardiac sodium current by decreasing the cell surface expression level of cardiac sodium channel Nav 1.5, but does not affect IKr potassium current. In conclusion, our results indicate that lamin A/C mutation p.Arg399Cys weakens the interaction between nuclear lamina (lamin A/C) and the nuclear pore complex (NUP155), leading to the development of AF. The findings provide a novel molecular mechanism for the pathogenesis of AF. Abstract : We have made a novel finding that lamin A/C interacts with NUP155, establishing an intricate link between nuclear lamina and nucleopore complexes. We further show that disruption of the lamin A/C‐NUP155 interaction is involved in the pathogenesis of atrial fibrillation (AF).